Community Behavior Regarding Waste Management in Slums (Case Study: Lamglumpang, Ulee Kareng, Banda Aceh) - Maisari, Lia; Fuady, Mirza; Safwan (Talenta Publisher, 2025)
In Banda Aceh, garbage is a significant concern. The trash problem requires the participation of the community. However, there are still numerous litterers, such as in the Gampong Lamglumpang, Ulee Kareng district. Gampong Lamglumpang is one of the villages identified as slums in Banda Aceh City. Poor waste management is a contributing factor to the slums. This study intends to assess the community's waste management practices in Gampong Lamglumpang and propose solutions to these issues. The study uses a descriptive quantitative by employing a questionnaire to collect data, which would be analyzed using Microsoft Excel. The data collection used the purposive sampling method. The sampling was up to sixty families. According to findings, many families were still burning their waste, indicating that their waste management was still insufficient. The author's suggestion for the government is to play a role in changing people's behaviour, such as by giving education and socialization of the 3Rs (reuse, reduce, and recycle) and by teaching the community how to transform garbage into something of economic worth. In addition, the Government must optimize waste transportation for must be optimized for the preservation of a clean environment.